M144 Acute Dietary Nitrate Supplementation Reduces The Oxygen Cost Of Submaximal Exercise In Copd. (10th November 2014) - Curtis, KJ; Tanner, R; O'Brien, K; Polkey, MI; Edwards, LM; Hopkinson, NS
Abstract : Introduction: The recognised link between plasma nitrite levels and exercise performance suggests a role for the nitrate-nitrite-nitric oxide pathway in facilitating exercise. Research in healthy individuals has demonstrated a reduction in the oxygen cost of exercise at submaximal workloads following nitrate supplementation. Dietary nitrate administration has been associated with reductions in blood pressure and augmented exercise performance. The effect of acute nitrate dosing on performance and metabolic parameters during cardiopulmonary exercise testing in COPD has not previously been investigated. Objectives: To investigate the hypotheses that acute nitrate dosing would improve exercise performance, reduce the oxygen cost of submaximal exercise performance and lower arterial blood pressure in COPD patients (GOLD stage II-IV). Methods: We performed a randomised, double-blind, placebo-controlled cross-over study comparing the effect of 140 ml of beetroot juice (containing 12.9 mmol nitrate) with a matched placebo of nitrate-depleted beetroot juice in COPD patients not receiving oral nitrates. Subjects were randomised to consume beetroot juice (BR) or placebo (PL) 3 h prior to endurance cycle ergometry, performed at 70% maximal workload assessed by a baseline incremental maximal, symptom-limited test. Blood pressure measurements were taken at baseline and immediately prior to the exercise test. After a washout period of a minimum of 7 days the protocol was repeated with the crossover beverage. Results: 25 COPD patients were recruited of whom 21 successfully completed the study (age 68 ± 7 years; BMI 25.2 ± 5.5 kg/m 2 ; FEV1 percentage predicted 50.1 ± 21.6%; peak VO2 during incremental cycle ergometry 18.0 ± 5.9 ml/min/kg). Diastolic blood pressure was significantly lowered by nitrate supplementation (-6.9 ± 7.8 BR vs. –1.4 ± 8.4 mmHg PL, p = 0.008). Nitrate supplementation significantly reduced oxygen consumption during equivalent isotime exercise (60–70% isotime 16.6 ± 5.6 BR vs. 17.1 ± 5.9 ml/min/kg PL, p = 0.017; 70–80% isotime 16.7 ± 5.7 BR vs. 17.2 ± 5.5 ml/min/kg PL, p = 0.010; 80–90% isotime 16.8 ± 5.7 BR, vs. 17.5 ± 5.75 ml/min/kg PL, p = 0.004). The endurance time was not significantly different between the groups (5.65 (3.90–10.40) BR vs. 6.40 (4.01–9.67) minutes PL, p = 0.50). Conclusion: The acute administration of nitrate reduces oxygen consumption and diastolic blood pressure during equivalent exercise in COPD patients.